Chapter 10: The social sources of unelected power: how central banks became entrapped by infrastructural power and what this can tell us about how (not) to democratize them - Walter, Timo (Edward Elgar Publishing, 2022)
The 'unconventional' monetary policies of the past decade have re-opened the debate about central banks' accountability and the nature and sources of their legitimacy. Unprecedented quantitative easing and asset purchasing programmes have demonstrated that central banks possess considerable 'infrastructural power' to influence the global economy, far beyond the narrow mission of price stability on which the Inflation Targeting regime as the global technical 'gold standard' of central banking had been premised. The obvious scope and apparent fungibility of these infrastructural powers have led to increasing pressures to repurpose monetary policy towards various socio-economic problems and challenges. What has been excluded from these debates is the question of the social conditions of central banks' infrastructural power and its (apparent) fungibility. In this chapter, I draw on sociological insights to show that central banks' technical power and agency rests on a precarious social embedding in global finance. I argue that attempting to realign monetary policy to serve other social goals, we risk eroding the very basis of its infrastructural power. For this reason, I end with a plea against developing monetary policy into a 'monopoly infrastructure' of macro-economic governance, and in favor of preserving a more healthy ecology of policy tools and infrastructures.